Brown Rice Consumption Effect on Blood Sugar Levels in Type-2 Diabetes Bibliometric Analysis - Zilva Karimah Azahra (Universitas Bakti Indonesia, 2023)
The bibliometric analysis aimed to explore brown rice consumption's impact on blood sugar levels, particularly for type 2 diabetes patients. It utilized Publish or Perish software and Google Scholar database alongside Microsoft Excel 2016 and VOSviewer for data visualization. Using keywords like